AN UPDATED PHARMACOLOGICAL OVERVIEW ON MOMORDICA CYMBALARIA (ATHALAKKAI)â€ - K, GOPALASATHEESKUMAR (Innoriginal: International Journal of Sciences, 2017)
The review was carried out to discuss in detail about pharmacological activities of Momordica cymbalaria. Momordica cymbalaria is belongs to the family of Cucurbitaceae. In this plant vegetables are used for food in southern countries. The phytoconstituents of alkaloids, carbohydrates, flavonoids, sterols, terpenoids and saponins are present in Momordica cymbalaria. In this review evaluate the various pharmacological activities of the Momordica cymbalaria. From the literature collections the Momordica cymbalaria was having the Anti-diabetic Activity, Hypolipidemic activity, Anti-diarrhoeal activity, Antiulcer activity, Neuroprotective Activity, Cardioprotective Effects, Hepatoprotective activity, Nephroprotective, Anti-Cancer Activity, Anticonvulsant activity, Anti-inflammatory activity, antiovulatory, abortifacient activity and Antimicrobial Properties. Key words: In vivo, Anti-diabetic, Saponins, Flavanoids, Animal model, Phytochemical Â 